Selection of Ideal Contraceptive Tool Using Hybrid Entropy-Topsis Method - Wahyu Handamari, Endang; Andawaningtyas, Kwardiniya; Karim, Corina (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2018)
The Hybrid Entropy-TOPSIS method is a combination of two methods, Entropy and TOPSIS. The combination of the two methods is used in the decision-making model to improve the quality of a decision. In this research, the Hybrid Entropy-TOPSIS method was applied to determine the ideal contraceptive tool based on the acceptor criteria. Entropy is a method of weighted criteria, while TOPSIS is a method of decision making through the alternative ranking process based on weighted criteria. The criteria are factors which influence to Keluarga Berencana acceptors for selecting contraceptives. The used criteria in this research were the age, blood pressure, menstrual cycle, the use of contraceptives, and the cost. While the Alternative is contraceptive tool itself. The selected alternatives here were Pill, Injection, Condoms, Implant, IUD and MOP / MOW. Based on the results of the questionnaire data and the simulation, it was obtained that pill and implants has the highest ranking and they indicated that pill and implants as an alternative selection of the ideal contraceptives.